(untitled) (Architecture Image Studies, 2026)
Philosophers throughout time have expressed their diverse concepts and visions of the state as a product of human society. One of these, Plato, considered the perfect state as an authority with absolute inviolability and inalienable immunity. In his philosophical research, he distinguished the essential role of laws in an organized society and particularly focused on the dual nature of these laws: both binding and punitive, as well as their curative role against moral evils in an organized society. Plato’s aristocratic origins served as the foundation of his political engagement in the society of his time. This circumstance, along with the acquisition of ideas from one of antiquity’s most prominent philosophers, Pericles, who attempted to democratize Athenian society, significantly influenced and shaped Plato’s philosophical worldview. Subsequently, he became part of the lineage of prominent Athenian thinkers, such as Socrates, Pythagoras, Parmenides, and Aristotle, who established the foundations of philosophical studies. Until his death, Plato remained Socrates’ student and colleague. This paper examines Plato’s ideas on politics, the state, and just government, focusing specifically on state organization and its division into social classes, the role of philosophers as leaders, and his reasons for believing that only such a government could ensure justice and well-being for all citizens.